2017
DOI: 10.13080/z-a.2017.104.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shading by coloured nets on yield and fruit quality of sweet pepper

Abstract: The concept of photo-selective netting was studied in a sweet pepper (Capsicum annuum L.) cultivar 'Cameleon' from summer cultivation in south Serbia (under high solar radiation 910 W m -2 , with a photosynthetic photon flux density of 1661 µmol m -2 s -1 ), under four different coloured shade-nets (pearl, red, blue and black) with 40% relative shading. The aim of the study was to determine how different environmental control technologies, coloured shade-nets as net house or plastic-house integrated with colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 31 publications
7
57
0
2
Order By: Relevance
“…Although the formation of carotenoids in mature fruits does not require induction by light, shaded fruits have lower content of carotenoids (Dorais and Papadopoulos, 2001). The carotenoid content was lowest in plants from open fields and highest in plants covered by black nets (Ilic et al, 2017). This study clearly showed that Chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids increased with increased shade level (Table 3).…”
Section: Vegetative Growth and Physiological Characteristicsmentioning
confidence: 52%
See 2 more Smart Citations
“…Although the formation of carotenoids in mature fruits does not require induction by light, shaded fruits have lower content of carotenoids (Dorais and Papadopoulos, 2001). The carotenoid content was lowest in plants from open fields and highest in plants covered by black nets (Ilic et al, 2017). This study clearly showed that Chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids increased with increased shade level (Table 3).…”
Section: Vegetative Growth and Physiological Characteristicsmentioning
confidence: 52%
“…Although shade-grown plants are not directly exposed to sunlight, they produce additional chlorophyll a and b to capture diffuse radiation to produce the carbohydrates needed for the plant to grow, as supported by the results of Beneragama and Goto (2010). Shaded lettuce leaves showed higher total chlorophyll (chlorophyll a and b) content than leaves from unshaded control plants (Ilic et al, 2017). Minimal chlorophyll fluorescence (F 0 ) has been reported to increase with the increase of the irradiance.…”
Section: Vegetative Growth and Physiological Characteristicsmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study, shade nets modified light quantity (i.e., PAR) received by bell pepper plants; the effect of shade net treatments on light quality was not measured. Black nets and colored nets have been reported to influence plant growth of bell pepper and other vegetables (Díaz-P erez, 2013; Ilic et al, 2017;Omb odi et al, 2015;Shahak, 2008). In greenhousegrown eggplant, plant height, leaf number, total leaf area, individual leaf area, and plant fresh weight were increased under shading compared with an open field (Aied et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Although black nets are most commonly used, there has been increased interest in colored nets. Colored nets may influence plant growth, yield, and fruit quality because of their ability to modify both light quality and quantity (Arthurs et al, 2013;Fallik, 2009;Ilic et al, 2017). Regardless of net color, shade nets reduce solar radiation with concomitant reductions in air, plant, and soil temperatures.…”
mentioning
confidence: 99%